Mystery in the sand eaudiobook - Warner, Gertrude Chandler (The Boxcar Children, 2012)
The Alden family is spending sunny days at the shore and summer nights in the mobile home right on the beach! One morning Benny finds a gold necklace in the sand, and a search for its owner begins a trail of clues that leads to Tower House, the strange old mansion nearby. What will the Boxcar Children find there?